1964
DOI: 10.2320/matertrans1960.5.225
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscope Observation of the Bainite of Carbon Steel

Abstract: The structure of the bainite in a 0.7% carbon steel has been studied by means of transmission electron microscopy and selected-area electron diffraction. The lower bainite consists of ferrite grains with internal fine cementite precipitates lying on one kind of planes (probably stacking fault planes). This behaviour of cementite is different from that of the tempered martensite, and moreover in the ferrite there are hardly seen any traces of the twin faults which are usually found in the martensite. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The axes of these carbides were inclined between 53 • and 62 • to the growth direction of the bainitic ferrite. It has been reported that the angle between carbides in the lower bainite ferrite inclines at about 60 • to the growth direction of ferrite, which is very close to the angles measured in the present investigation [30]. It should also be noted that in agreement with reported results in the literature, the morphology of decomposed retained austenite blocks is very similar to that of lower bainite [31].…”
Section: Microstructural Evolution During Temperingsupporting
confidence: 92%
“…The axes of these carbides were inclined between 53 • and 62 • to the growth direction of the bainitic ferrite. It has been reported that the angle between carbides in the lower bainite ferrite inclines at about 60 • to the growth direction of ferrite, which is very close to the angles measured in the present investigation [30]. It should also be noted that in agreement with reported results in the literature, the morphology of decomposed retained austenite blocks is very similar to that of lower bainite [31].…”
Section: Microstructural Evolution During Temperingsupporting
confidence: 92%
“…The diameter L q in aB is, then, given by: It is reported that cementite within bainitic ferrite has orientation relationship with bainitic ferrite. 19,20) This is caused by decreasing the interfacial energy, which is dealt as one of fitting parameters in this model.…”
Section: Cementite Precipitation In Bainitic Ferritementioning
confidence: 99%
“…From the viewpoint of the industrial development of bainite steel, transformation behavior under continuous cooling conditions needs to be clarified. However only little has been studied with respect to the effects of these factors mentioned above under continuous cooling conditions.6) Two different models, diffusional7-9) and displacive mechanisms, [10][11][12] Relationship between the hardness of transformed products and the 50 '/* transformation temperature in steel 2.…”
Section: Introductionmentioning
confidence: 99%